Skin Biopsy in Netherton Syndrome: A Histological Review of a Large Series and New Findings. (February 2016) - Leclerc-Mercier, Stephanie; Bodemer, Christine; Furio, Laetitia; Hadj-Rabia, Smail; de Peufeilhoux, Laetitia; Weibel, Lisa; Bursztejn, Anne-Claire; Bourrat, Emmanuelle; Ortonne, Nicolas; Molina, Thierry Jo; Hovnanian, Alain; Fraitag, Sylvie
Abstract : Abstract: Netherton syndrome (NS) is a severe genetic skin disorder, with often delayed or misleading clinical signs. The histological features of skin biopsies, usually described as a psoriasiform hyperplasia, have only been reported in isolated case reports or small case series. The aim of this study is to define, for the first time, the precise histological pattern of cutaneous lesions, in a large cohort of skin biopsies from confirmed NS patients. The study included 80 consecutive skin biopsies from 67 patients taken between January 1995 and June 2014. All were from confirmed NS patients with either a negative lympho-epithelial Kazal-type–related inhibitor (LEKTI) immunohistochemistry and/or molecular confirmation by identified mutation in SPINK5 . In this cohort, the most frequent histological finding was also psoriasiform hyperplasia, but there were additional, less common, or previously unreported findings, including compact parakeratosis with large nuclei, subcorneum or intracorneum splitting, presence of clear cells in the upper epidermis or stratum corneum, dyskeratosis, dermal infiltrate with neutrophils and/or eosinophils, and dilated blood vessels in the superficial dermis. An early confirmation of the diagnosis of NS is essential for improved patient management. Thus, in the situation of a patient with an unknown skin disorder and non specific clinical presentation, the dermatopathologist may now be able to suggest the diagnosis of NS based on these newly reported characteristics. However, LEKTI immunohistochemistry remains the essential diagnostic investigation in cases with misleading or nonspecific histological features and is mandatory for the definitive diagnosis of NS in all patients.